Persepsi Mahasiswa PGSD terkait Model Problem-Based Learning dalam Pembelajaran IPAS: PGSD Students’ Perceptions of the Problem-Based Learning Model in IPAS Learning - Nafhan Maulana Ashary; Irma Inesia Sri Utami (Program Studi Tadris Ilmu Pengetahuan Sosial (TIPS) UIN Datokarama Palu, 2025)
This study explores the perception of Elementary School Teacher Education (PGSD) students of Djuanda University towards the Problem-Based Learning (PBL) model in Natural and Social Sciences (IPAS) learning. The main objective is to analyze students' understanding of the concept of PBL, its effectiveness in learning IPAS, and its relevance to teaching practices. The research uses a qualitative descriptive approach, this study involves three PGSD students as subjects. Data was collected through in-depth interviews and open-ended questionnaires, then analyzed using triangulation techniques to identify patterns and meanings. The results of the study show that PGSD students have a strong understanding of PBL as a student-centered approach that is authentic problem-based, effective in developing critical thinking and problem-solving. They perceive PBL to be very effective in increasing student involvement and understanding of IPAS concepts in a concrete way, and is very relevant to the characteristics of IPAS which focuses on everyday issues, despite minor implementation challenges. These findings confirm PBL as an effective pedagogical strategy suitable for IPAS, potentially improving the quality of teaching and equipping students with essential skills. This study is expected to contribute to the development of a more optimal teacher education curriculum and training program.